The Analysis of Credit Policy Development in Bank AAA (Case of Implementation New Policy Architecture) (The Indonesian Journal of Business Administration, 2013)
Bank AAA as one of the largest and oldest private bank in Indonesia. Based on audit findings form Bank Indonesia, it stated that there are inconsistencies in credit policies between one credit policy to other credit policies. This leads to the NPL to be faced by the Bank, which in turn makes banks set large allowance as well. This of course will affect the capital requirements that must be owned by the Bank. Moreover, it causes different perceptions of credit policy that make the process in credit activities become not standard. This inconsistencies also leads to create different perception in doing credit activity process and credit policies. To resolve those two problems, author proposes and idea in credit policy development in a framework of credit policy development that contains of three big phase, pre-development, development and pre-development phase. Author is responsible in implementing the framework with three phases. The purpose of the framework is to have an integrated and structured credit policy. To minimize this, Bank Indonesia issued a new policy relating to capital adequacy is calculated based on the risk profile of each bank. Based on this, the bank that has large bad debt will automatically have the potential for credit risk and the greater the loss. In line with this, Bank AAA applies new policy architecture in bank-wide basis, where all existing policies have to be reconstructing especially in terms of content. With the implementation of the new policy is expected to help the parties who involve in lending activities and will ultimately reduce the amount of bad debt held by the Bank. The next step should be done by the Bank after having a policy is the attestation and monitoring of compliance in carrying out the things that are listed in the credit policy.Â Keywords: Risk Management, Credit Policy, Policy Architecture